The Magic of Brand Experience: A Value Co-creation Perspective of Brand Equity on Short-form Video Platforms - Athapol Ruangkanjanases; Asif Khan; Ornlatcha Sivarak; Untung Rahardja; Shih-Wen Chien; Shih-Chih Chen (Ital Publication, 2023)
Many companies are utilizing short-form video platforms to enhance the value co-creation between brands and consumers and ultimately create brand equity. However, there is a research gap in the present literature regarding the significance of consumers' participation in short-form video platforms affecting corporate brand equity. The present study aims to address this research gap by incorporating value co-creation theory to investigate the role and mechanism of value co-creation generated by consumer participation in short-form video platforms, i.e., corporate-initiated value co-creation and customer-initiated value co-creation, on corporate brand equity. The current study used a survey methodology to collect 481 samples from TikTok users using a convenience sampling method. The present study used structural equation modeling on the collected data. The findings show that corporate-initiated value co-creation can positively influence corporate brand equity, in which brand experience plays a partially mediating role. Customer-initiated value co-creation can also promote brand equity, whose role is also partially mediated by brand experience. This study theoretically contributes to the value co-creation concept and its theoretical association with brand equity and brand experience. This research also offers practical implications for practitioners regarding the utilization and enhancement of brand experience to improve clients' engagement in value co-creation activities. Doi: 10.28991/ESJ-2023-07-05-09 Full Text: PDF